What we already know about rhubarb: a comprehensive review - Xiang, Hong (Chin Med, 2020)
Rhubarb (also named Rhei or Dahuang), one of the most ancient and important herbs in traditional Chinese medicine (TCM), belongs to the Rheum L. genus from the Polygonaceae family, and its application can be traced back to 270 BC in “Shen Nong Ben Cao Jing”. Rhubarb has long been used as an antibacterial, anti-inflammatory, anti-fibrotic and anticancer medicine in China. However, for a variety of reasons, such as origin, variety and processing methods, there are differences in the effective components of rhubarb, which eventually lead to decreased quality and poor efficacy. Additionally, although some papers have reviewed the relationship between the active ingredients of rhubarb and pharmacologic actions, most studies have concentrated on one or several aspects, although there has been great progress in rhubarb research in recent years. Therefore, this review aims to summarize recent studies on the geographic distribution, taxonomic identification, pharmacology, clinical applications and safety issues related to rhubarb and provide insights into the further development and application of rhubarb in the future.